Isolation, purification and molecular characterization of the putative asparaginyl-tRNA synthetase cDNA of Schistosoma japonicum - Pinlac, Ma. Theresa Sarmiento-
The current study was undertaken as part of a bigger project for new drug discovery for parasitic diseases. Specifically, this study aimed to determine the sequence of the putative asparaginyl-tRNA synthetase (AsnRS) cDNA of Schistosoma japonicum (Sj), deduce its resulting amino acid sequence, compare both sequences with the respective human and Brugia malayi (Bm) AsnRS sequences, determine the predicted functions of the deduced Sj polypeptide, and compare its protein domains with the human Bm AsnRS domains. The possible sequence of the schistosomal AsnRs was first constructed a series of sequence searches and alignments that initially used the know sequence of the BmAsnRS. Different combinations of gene-specific primers (GSP) designed from the constructed sequence were then used in the attempts to isolate the desired cDNA from a Sj cDNA library. After optimization of thermal cycling conditions, a full-length cDNA containing the entire coding sequence of the putative S. japonicum AsnRS was amplified. This was cloned and subsequently sequenced. From the obtained 1749=based cDNA sequence, the probable amino acid sequence was deduced using the Transeq program, which revealed a 546-residue polypeptide. Both the cDNA and the deduced amino acid sequences of the putative Sj AsnRS were compared with the respective sequences of human Bm AsnRS using the Emboss and ClustalW programs, revealing up to 73% similarity. Structural analysis through ProDom queries of the amino acid sequences of the Brugia malayi and human AsnRS and that of the polypeptide deduced from the isolated Sj cDNA revealed 4 domains identical to all the 3 polypeptides, while functional analysis done through an InterPro query of the deduced Sj amino acid sequence revealed that it contains domains with tRNA ligase activity for tRNA aminoacylation and domains for nucleic acid binding. The evidences provided by the results strongly suggests that the Sj AsnRS cDNA had indeed been isolated. With the sequence of the full-length SjAsnRS cDNA now known, new opportunities for the discovery and development of a new drug against Schistosoma japonicum have been opened.